2017
DOI: 10.12982/ajtr.2017.0011
|View full text |Cite
|
Sign up to set email alerts
|

Gastronomic experience as a community development driver: the study of Amphawa Floating Market as community-based culinary tourism destination

Abstract: This paper investigates the connection between culinary tourism and community development through a case study of Amphawa Floating Market, a touristic evening market in Samutsongkram, Thailand, that has been developed in an economically depressed historic trade community. It aims to examine the role of gastronomic experiences offered in the market as a means of improving the well-being of local residents, and critically discuss the potential for the market to become a viable community-based culinary tourism de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…How it can be promoted and supported as a supplement to tourism, especially during and post the COVID-19 pandemic period. Many researchers in Thailand attempted to study for confirmation that gastronomic tourism needs to be promoted and supported more than now, such as Kivela and Crotts (2006), Citrinot (2018), Lunchaprasith (2018), and Promnil et al (2021). Furthermore, Kattiyapornpong et al (2021) proposed that during the COVID-19 pandemic, gastronomic tourism, particularly gastronomic experiences, is important to drive tourist spending via platforms offering virtual gastronomic tourism activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How it can be promoted and supported as a supplement to tourism, especially during and post the COVID-19 pandemic period. Many researchers in Thailand attempted to study for confirmation that gastronomic tourism needs to be promoted and supported more than now, such as Kivela and Crotts (2006), Citrinot (2018), Lunchaprasith (2018), and Promnil et al (2021). Furthermore, Kattiyapornpong et al (2021) proposed that during the COVID-19 pandemic, gastronomic tourism, particularly gastronomic experiences, is important to drive tourist spending via platforms offering virtual gastronomic tourism activity.…”
Section: Discussionmentioning
confidence: 99%
“…The word ''gastro'' refers to the stomach, and ''nomos'' means knowledge (Scarpato, 2002). Many researchers around the world have already confirmed that gastronomic tourism has a high potential being a new trend tourism movement activity to support tourism industry development sustainably (Citrinot, 2018;Kivela & Crotts, 2006;Lunchaprasith, 2018;Promnil et al, 2021;Rimdusit & Duangsaeng, 2019). Suanpang (2015) also proposed that gastronomic tourism is a high-potential new trend in tourism activity in ASEAN.…”
Section: Introductionmentioning
confidence: 99%
“…The primary motivation of tourists (15% of total) is to choose an area rich in local foods (FITUR) [28], but the World Tourism Organization (WTO) is concerned with insufficient promotion of gastronomic tourism. After culture and natural landscapes, gastronomy tourism comes third for tourists to visit and consume local foods [29]. More than 2 million foreigners visited Pakistan in 2017, with the majority visiting the country's northern areas (see the Appendix B for northern areas).…”
Section: Of 17mentioning
confidence: 99%
“…A series of participatory projects undertaken by public and private agencies-including municipal government, universities, companies, NGOs, local stakeholders, the Chaipattana Foundation and the Danish International Development Assistance-developed from 2001 onward, have restored traditional waterfront architecture and promoted activities to encourage gastronomic tourism, showcase cultural heritage and re-stimulate market culture (Silapacharanan and Dupuy 2011;Peerapun 2012;Peerapun et al 2006). Traditional culinary resources and food-growing methods were used as unifying strategies to encourage self-reliance, bring a sense of pride back to the community and reinvigorate a languishing local economy (Lunchaprasith 2017). Participatory planning meetings, led by the mayor, resulted in a municipal-level organizational structure to register and manage vendors.…”
Section: Overview Of Casesmentioning
confidence: 99%